Cover Feature: Towards Zwitterionic Oligonucleotides with Improved Properties: the NAA/LNA‐Gapmer Approach (ChemBioChem 22/2020). (28th October 2020) - Wojtyniak, Melissa; Schmidtgall, Boris; Kirsch, Philine; Ducho, Christian
Abstract : The cover feature picture shows our work on a gapmer oligonucleotide with a zwitterionic backbone structure in the central gap and two anionic outer segments. One key question was if and how such a gapmer would bind to RNA, that is, if it displays sufficient binding affinity and base‐pairing fidelity. The other key question was if it would be stable towards nuclease‐mediated degradation. Our paper reports on the favourable properties of the zwitterionic gapmer oligonucleotide regarding these and further aspects. More information can be found in the full paper by C. Ducho et al.